Marguerite S. Anderson journal - Anderson, Marguerite S.
Volume (479 pages) containing the records and events of the retracing of Captains Meriwether Lewis' and William Clark's expedition on the 150th anniversary of that event.
Collection material in English.
Keywords: Lewis, Meriwether, -- 1774-1809.; Clark, William, -- 1770-1838.